Boosting the Cycle Life of Aprotic Li–O2 Batteries via a Photo‐Assisted Hybrid Li2O2‐Scavenging Strategy. Issue 2 (11th December 2017) - Qiao, Yu; Liu, Yang; Jiang, Kezhu; Li, Xiang; He, Yibo; Li, Qi; Wu, Shichao; Zhou, Haoshen
Abstract: The development of the nonaqueous Li–O2 battery, a promising candidate for high‐gravimetric‐energy‐storage techniques, is seriously restrained by the high charge overpotential during electrochemical decomposition of insulating Li2 O2 . Benefiting from the photovoltage, photo‐assisted charging is revealed as a feasible method to reduce the charge potential. However, a long period of illumination will inevitably aggravate the degradation of the electrolyte. Herein, composed of contact‐ion‐pairs (CIPs), a newly introduced superconcentrated electrolyte presents superior stability against parasitic photocatalytic decomposition. More significantly, the conventional and photo‐assisted charging processes are rationally integrated as a unique hybrid strategy, in which the highly polarized charging stage is replaced by the photo‐assisted Li2 O2 ‐scavenging process. By tuning the photocatalysis and Li2 O2 electrochemical oxidization, the hybrid Li2 O2 ‐scavenging strategy not only boosts the cycle life of rechargeable Li–O2 batteries but also opens possibilities in designing photocatalysis‐involved rechargeable energy‐storage battery systems. Abstract : The photo‐assisted charging process presents an effective Li2 O2 ‐scavenging approach for Li–O2 batteries. In a newly designed hybrid strategy, the conventional charging and photocatalysis‐involved procedures are rationally integrated, in which the highly polarized charging stage is substituted. The hybrid strategy not only boosts the cycleability of Li–O2 batteries but also extends the design principle for integrating solar cells and Li‐based batteries.